Research of Wood-Polymer Compositions of DMTA Methods - Nicolas Pjanic (International Journal of Science and Society, 2020)
The article presents the results of polymer-wood composites, as well as the excretion of tritium woods and leaves. The base of the composite was made of thermoplastic polypropylene. Three composites prepared by the volume of filling content (25, 50 and 70%) and the various fractions of the used slags were prepared for research. The test is prepared with the use of spray technology. One of the methods of thermal DMTA analysis is used for research. Accompanied studies of dynamic mechanical properties have been chosen to determine the effect of filling and the size of the traces on the properties of the cured composites. The obtained results were invited to determine the design of these materials, as well as the determination of the amount and the alternative level for materials applied to large-scale elements made of polymeric materials.